The Incorporation and Reduction of Value Judgements in Systems - Mattessich, Richard (Management Science, 1974)
This paper first examines and illustrates the way in which value judgements can be incorporated in a system, and how they can be externalized by changing the system's boundaries. Then some general statements about value judgements and their locations in systems are advanced. The acceptance of these statements enables an extension of the notion of “value judgement” from sentences to systems. Thus criteria are spelled out for attributing the terms “normative” and “positive” to systems. Then the changes are examined which occur when a system undergoes the transfer of a value judgement from its structure to its (external) environment. Furthermore an attempt is made to clarify (by means of this Method of Neutralizing Systems) the longstanding controversy of value neutrality of science and of our own discipline. Finally an analysis is sketched which reveals that the assertion “ought-to-sentences cannot be reduced to is-sentences” need not be tautological if it is meant to hold within a system only. If the pertinent normative remnant lies beyond the system boundaries, a value judgement can indeed be reduced to a factual statement, but merely within this system.